2021
DOI: 10.18051/univmed.2021.v40.3-13
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of diabetes comorbidities in Indonesia: a cohort study of non-communicable disease risk factor

Abstract: Background<br />Type 2 diabetes mellitus (DM) is a non-communicable disease that constitutes a huge health burden, with the presence of comorbidities of DM adding to it. This study aimed to obtain the main determinants of the combined incidence of DM and its main comorbidities in adults.<br /><br />Methods<br />This was a further analysis of the Non-Communicable Disease Risk Factor Cohort Study 2011 – 2018 involving 3730 subjects. Data of diabetes-free respondents at baseline were follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Previous research has stated that the risk factors for NCDs are behavioral, metabolic, and socio-demographic. 2,[12][13][14][15][16] Unfortunately, these previous studies were only conducted at the city level, 13,14 only involved adolescent respondents, 16 and only examined DM as NCDs. 12 The modernization of food in the Indonesian diet, such as the introduction of instant food and energy drinks, 17 has not been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has stated that the risk factors for NCDs are behavioral, metabolic, and socio-demographic. 2,[12][13][14][15][16] Unfortunately, these previous studies were only conducted at the city level, 13,14 only involved adolescent respondents, 16 and only examined DM as NCDs. 12 The modernization of food in the Indonesian diet, such as the introduction of instant food and energy drinks, 17 has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…2,[12][13][14][15][16] Unfortunately, these previous studies were only conducted at the city level, 13,14 only involved adolescent respondents, 16 and only examined DM as NCDs. 12 The modernization of food in the Indonesian diet, such as the introduction of instant food and energy drinks, 17 has not been studied. This study aimed to analyze the modifiable, non-modifiable, and physiological risk factors of NCDs in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…(16) The proportion of subjects with high LDL concentration (100 mg/dL and above) at baseline and in monitoring years 2, 4 and 6, was found to be higher than 80%. (17) Multivariate analysis of the study of Chen et al (18) found a significant association between psychological distress and dyslipidemia, with a hazard ratio (HR) of 1.14 (95% CI: 1.04-1.25). On the other hand, the results of the study of Zhang et al (19) showed that the group with mental health disorders had a significant relationship for awareness of dyslipidemia, with odds ratio (OR) =1.81, but not for treatment of dyslipidemia (OR=1.29) and for controlled dyslipidemia (OR=0.93).…”
Section: Introductionmentioning
confidence: 99%